Non-surgical embryo transfer in goats and sheep: the Brazilian experience - Fonseca, Jeferson F.; Oliveira, Maria Emilia F. [UNESP]; Brandao, Felipe Z.; Batista, Ribrio I. T. P.; Garcia, Alexandre R.; Bartlewski, Pawel M.; Souza-Fabjan, Joanna M. G. (Csiro Publishing, 2019)
Brazil has presented tremendous progress in non-surgical embryo transfer (NSET) in sheep and goats. New instruments and techniques for non-surgical embryo recovery (NSER) and NSET in small ruminants were implemented. Recent improvements include refinement of the protocols for cervical relaxation combining oestradiol-oxytocin-cloprostenol treatment at specific times before NSER in sheep; recipient goats do not require any hormonal drugs to induce cervical dilation and direct embryo transfer by the cervical route yields excellent results. Transrectal ovarian ultrasonography (B-mode but especially colour Doppler) have proven to be accurate methods to localise and enumerate corpora lutea and luteinised unovulated follicles in recipient and donor does and ewes. An array of new criteria for selecting superior animals for NSER and NSET (e.g. cervical mapping) have been developed by Brazilian researchers. Extensive studies on both technologies were initially conducted in commercial breeds of goats and sheep but have been gradually extended to some native breeds of sheep (germplasm conservation) and dairy goat operations. It is speculated that, in future, NSER and NSET may become methods of choice for caprine and ovine embryo recovery and transfer in Brazil, and then globally. Due primarily to the efficiency of NSET in goats, a novel interspecies (e.g. bovine) IVP method may soon be developed on a large scale. The Brazilian experience is an invaluable source of information and know-how promoting the replacement of conventional surgical assisted reproductive technologies with non-surgical procedures and hence supporting the rapid development of the embryo transfer industry in small ruminants.
Keywords: cervical route; invivo embryo production; multiple ovulation and embryo transfer (MOET); small ruminants; transcervical embryo collection